Role of Forestry in Mitigating the Energy Crisis Tn India - Singh, Bakhshish (Indian Forester, 1973)
The world demand for energy doubles every 13 years or so. At the present rate of use of fossil fuels, all the world resources are likely to be exhausted in 50 to 100 years period. For a population of about 550 million, the total domestic energy consumption in India is about 190 million tons of coal equivalent. The prime coking coal reserves of India are expected to be exhausted in about 40 years. The desirable approach to the problem of likely energy crisis would be to rely more and more on renewable resources like fuelwood and to conserve the stored resources of non renewable fossil fuels like coal, mineral oils and nuclear fuels etc. for emergent and specific uses only. Solar energy can very cheaply be tapped through the agency of plants and there is a dire need to develop our fuelwood resources through intensive management of existing forests and by creating fuelwood plantations of fast growing tree species over wastelands, village common lands, and other available areas. Tree plantations will also be helpful in environmental conservation and in reducing the hazards of pollution.